Open innovation and firms performance: state of the art and empirical evidences from the bio-pharmaceutical industry. (2016) - Mazzola, Erica; Bruccoleri, Manfredi; Perrone, Giovanni
The research presented in this paper explores the effect of inbound, outbound and coupled open innovation practices on firms' performances in the biopharmaceutical industry. Specifically, although existing researches on open innovation effectiveness have separately investigated the effect of open innovation practices on innovation and financial performance, this study evaluates the concurrent effect of these practices on both such performance dimensions in a single framework. We state the importance for a manager to explore concurrently the influence of specific open innovation practices both on innovation and economic-financial performance. We empirically test our framework on a sample of 120 companies listed on the NASDAQ biotechnology index.